Study of Morphological Variations of The Human Ear for its Applications in Personal Identification - Khalid, Miraj; Ali, Shahid; Shah, Waseem; Akbar, Fazal; Israr, Muhammad; Asadullah; Hussain, Zahid; Iqbal, Arshad; Ahmad, Nisar; Khan, Ishaq; Khan, Wajid; Rahat, Murad Ali (Indus Journal of Bioscience Research, 2025)
The external human ear is considered to be a remarkably diverse structure, displaying a wide array of personal and morphological traits across different individuals and demographic groups. The study evaluates ear morphological features in a Swat district population; involving 54.2% males and 45.8% females aged 15-60. Vernier Caliper was used for measurement and Sony Cyber-shot DSC-H55 camera for morphological study. The study analyzed ear characteristics such as size, shape, anti-tragus shape, posterior helix rolling, Darwin tubercle, crus helix expression, and ear protrusion. It also examined ear length, breadth, concha length, and width. To find relation between the gender and different ear features statistical Pearson correlation test was used. The study revealed that both sexes had ear types like square, tongue, and triangular, with asymmetry in shape and tragus form. Individual differences were observed in earlobe structures, with half being unattached. The earlobe’s size and shape vary by gender, with males having longer lift ear tragus and females having equal lift ear lengths above and below the tragus. Both sexes have distinct ear widths and sizes. The height of the lift ear and the concha length varied according to gender as well. There are reports of differences in both sexes’ lift ear width and height. The right ear’s total length varies across the sexes. The right ear’s ear length is different above the tragus but similar below it. The length of the breadth varies across the sexes. The dimensions of the concha vary depending on the gender. In both sexes, the height of the lobes is comparable, but the width varies. Darwin’s tubercle displayed a range of structures. Most of the both ear length of parameters is significantly associated with gender. The current study concludes that the unique traits of the ear can yield highly valuable data for forensic examinations, including personal identification. A range of features and personalities can be seen in the ear’s form as well as in key components such as Darwin’s tubercle, helix, tragus, and earlobe.